Teaching Grammar to Achieve Communicative Competence - Rawsthorne, Daniela (Univerzita Pardubice, 2010)
This paper deals with the issue of teaching grammar to achieve communicative competence with EFL students. It presents and discusses arguments for and against teaching grammar, as well as various approaches and tips for improving the quality of teaching grammar towards achieving communicative competence.
Výuka gramatiky pro dosažení komunikativní kompetence
Keywords: komunikativní kompetence; Gramatika; výuka angličtiny; communicative competence; English language teaching; Grammar